Application of Qijiao moxibustion for patients with insomnia after stroke (气交灸在中风后失眠患者中的应用研究) - XU Qian (徐倩); DU Jing (杜静); GOU Yanhua (缑燕华); YU Hong (余红); ZHANG Fan (张帆) (中西医结合护理)
Objective To investigate the effect of Qijiao moxibustion for patients with insomnia after stroke. Methods Totally 80 patients with insomnia after stroke were randomly divided into the control group and the observation group, with 40 cases in each group. All patients received routine care, and those in the observation group were given Qijiao moxibustion. The Pittsburgh Sleep Quality Index (PSQI) and Athens Insomnia Scale (AIS) were used to evaluated the sleep quality of patients. Results There was no significant difference in PSQI score and AIS score between two groups before intervention (P＞0. 05). The PSQI score and AIS score were decreased after intervention, and were lower in the observation group than those in the control group (P＜0. 05). Conclusion Qijiao moxibustion is potentially effective to improve the sleep quality of patients with insomnia after stroke. (目的 探讨气交灸在中风后失眠患者中的应用效果。方法 中风后失眠患者80例随机分为对照组40例和观察组40例。对照组采用常规护理, 观察组在对照组基础上实施气交灸。比较2组干预前及干预后的匹兹堡睡眠质量指数 (PSQI)和阿森斯失眠量表(AIS)得分。结果 干预前2组AIS和PSQI评分比较, 差异无统计学意义(P＞0. 05)。干预后2组AIS和PSQI评分较干预前降低, 且观察组AIS和PSQI评分低于对照组, 差异有统计学意义(P＜0. 01)。结论 气交灸能有效改善中风后失眠患者的睡眠质量。)